The Effect of Implementation of Construction Safety Management Sytem on The Level of Work Accidents - Sri Defila; Kusumo Drajad S.; Kartika Hapsari S. (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2023)
The high number of construction accidents in infrastructure development projects in Indonesia is caused by the risk of danger that exists at every stage of construction. The implementation of the Construction Safety Management System (SMKK) is a manifestation of the labor protection system and for construction work, SMKK can minimize and avoid the risk of fatal work accidents. This study aims to determine the effect of the application of SMKK elements on the level of work accidents and find out the elements that greatly affect the level of work accidents in the X Toll Road Construction Project. Data collection methods are the distribution of questionnaires and interviews. Data analysis was performed using statistical analysis, namely multiple linear regression analysis. From the results of the study, based on the partial hypothesis test, it was obtained that the application of SMKK elements that partially affect the level of work accidents is the 3rd element, namely Construction Safety Support, while the other 4 elements do not have a significant influence on the level of work accidents and based on simultaneous hypothesis tests, it is obtained that the simultaneous application of SMKK elements has a significant influence on the level of work accidents. The results of the multiple regression equation show that the construction safety support element with a negative value means that it has the greatest influence that gives the possibility of work accidents occurring low compared to other SMKK elements.